Building an Interdisciplinary Framework for Global Health Solutions: A Qualitative Study - Sitti Zakiyyah Putri (Edukasi Ilmiah Indonesia, 2026)
Introduction: Global health challenges are becoming increasingly complex as they are shaped by the dynamic interaction of biomedical, social, economic, environmental, and political determinants. Persistent health inequities, fragile health systems, and emerging global threats have demonstrated the limitations of conventional discipline-specific approaches. Although interdisciplinary approaches are widely promoted as essential for addressing these challenges, there remains a lack of empirically grounded frameworks that clearly operationalize interdisciplinarity in global health practice. Methods: This study employed a qualitative research design using an interpretive descriptive approach to explore how interdisciplinary collaboration is understood, practiced, and sustained in global health contexts. Semi-structured, in-depth interviews were conducted with 50 purposively selected stakeholders representing diverse disciplinary backgrounds, including public health, clinical practice, social sciences, economics, environmental health, and policy. Participants were selected based on their professional experience and involvement in interdisciplinary global health initiatives. Data were analyzed using thematic analysis, applying both inductive and deductive coding to identify recurring patterns, relationships, and key themes that informed the development of an interdisciplinary framework. Results: Six core themes emerged from the analysis. Global health was understood as a complex, multidimensional system that requires integrated approaches across disciplines. Interdisciplinarity was perceived as both a mindset and a practical process, emphasizing shared problem framing, complementary disciplinary contributions, and iterative knowledge integration. Inclusive leadership and supportive institutional and policy environments were identified as critical enablers of effective collaboration, while structural silos, disciplinary hierarchies, and power imbalances remained persistent barriers. These findings demonstrate that interdisciplinarity in global health is a practical necessity rather than a purely conceptual ideal. Conclusion: This study concludes that strengthening global health outcomes requires the institutionalization of interdisciplinary approaches that integrate diverse forms of knowledge, promote shared problem framing, and address power imbalances across disciplines. The proposed empirically grounded framework offers a practical foundation for advancing integrated, context-sensitive, sustainable, and scalable global health solutions across diverse settings.